Analisis Masalah Kesehatan Pada Program Hipetensi di Dinas Kesehatan Kota Kediri Tahun 2024 - Sari, Maulidina; Wahyuni, Chatarina Umbul; Rahayu, Tiwuk Puji (Jurnal Epidemiologi Kesehatan Komunitas, 2025)
Background: The prevalence of hypertension in Indonesia in 2023 reached 30.8%, but only 18.9% of cases were under control, still below the national target of 63%. In Kediri City, although the coverage of hypertension services reached 100%, only 33% of patients managed to control hypertension. This study aims to identify problems, determine priorities, analyze causes, and formulate alternative solutions for hypertension programs.Methods: This descriptive observational study was conducted from July 8 to August 2, 2024. The study subjects were 30 people consisting of staff of the Health Office, Puskesmas and health cadres in Kediri City. Data were collected through brainstorming, in-depth interviews, and document studies. Problem prioritization was conducted using Urgency, Seriousness, Growth (USG) method, root cause analysis using epidemiological model, and alternative solutions using CARL (Capability, Accessibility, Readiness, Leverage) methodResults: Prioritization with the USG method that has the highest score is the low achievement of controlled hypertension. In 2023, the achievement in Kediri City was 33% increasing to 48% in January-June 2024, but still below the national target of 90%. The South Region health center has the lowest achievement of 31.8%. The main causes are low patient participation in routine control, high workload of health workers, and lack of family support. Alternative solutions include routine socialization, family assistance, and monitoring of control schedules through WhatsApp groups.Conclusion: The Kediri City Health Service is expected to conduct socialization with family support assistance. Keywords: Controlled Hypertension, Kediri, Problem Analysis.